1997
DOI: 10.1002/jobm.3620370108
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the thickness of the boundary layer surrounding bacterial PHA inclusion bodies, and implications for models describing the molecular architecture of this layer

Abstract: The thickness of the boundary layer surrounding polyhydroxyalkanoic acid (PHA) inclusion bodies in bacteria was determined from electron micrographs of ultrathin cell sections. The obtained values were compared with the thickness of boundary layers of other kinds of prokaryotic inclusion bodies known to be monolayers (sulfur globule, hydrocarbon‐containing inclusion, carboxysome, gas vesicle, chiorobium vesicle) and the thickness of typical bilayer membranes (cytoplasmic membrane, photosynthetic vesicle). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
39
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 20 publications
5
39
1
Order By: Relevance
“…The second explanation is that in prior studies, the envelope was removed by the EM preparation procedure, leaving only the network and the crystalline lamellar layer, which would constitute an electron-dense layer that is approximately 4 nm thick. Therefore, when previous studies reported the boundary layer as being 4 nm thick (21), it may be that the network/lamellar shell was being measured. It is well established that EM preparatory procedures are deleterious to membranes and related attached structures (5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second explanation is that in prior studies, the envelope was removed by the EM preparation procedure, leaving only the network and the crystalline lamellar layer, which would constitute an electron-dense layer that is approximately 4 nm thick. Therefore, when previous studies reported the boundary layer as being 4 nm thick (21), it may be that the network/lamellar shell was being measured. It is well established that EM preparatory procedures are deleterious to membranes and related attached structures (5).…”
Section: Discussionmentioning
confidence: 99%
“…Because of this, some researchers suggested that instead of an outer phospholipid layer, a protein layer, most logically composed of PhaP with embedded synthesis and depolymerizing enzymes, covers the inclusion (14,27). For a period of time, the difference between these two models seemed to be somewhat clarified by the determination by researchers that the outermost layer is 4 nm thick (21). This implies that it cannot be a lipid bilayer, which has been measured at 7 to 13 nm for C. necator H16 (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Phasins occur in any PHA SCLaccumulating bacterium, and are analogues of oleosins, which are bound to the surface of the oleosome in plants (Wieczorek et al, 1995;Steinbüchel et al, 1995;Wieczorek & Steinbüchel, 1996;Mayer & Hoppert, 1997;Hanley et al, 1999). Hitherto, only one phasin (PhaP1) has been known to occur in R. eutropha.…”
Section: Introductionmentioning
confidence: 99%
“…eutropha H16 has not yet been identified. However, PHB granules, as well as TAG inclusions, possess a hydrophobic core of the polyester or lipid, respectively, which is thought to be surrounded by a monolayer of phospholipids (de Koning & Maxwell, 1993;Hocking & Marchessault, 1994;Mayer & Hoppert, 1997;Wältermann et al, 2005). This common structure allows the targeting of PhaP1 to PHB granules and also TAG inclusions, as demonstrated in this study.…”
Section: Discussionmentioning
confidence: 99%